KAJIAN PARK AND RIDE UNTUK BUSWAY JAKARTA - Muhammad Nanang Prayudyanto; Ofyar Z. Tamin (Jurnal Transportasi, 2007)
Abstract As one of the TDM alternative for improving bus public transport services, park-and-ride (P&R) could support a larger mode shift from private car users. Experience from other developed countries proves that P&R could bring more passenger uses mass transit system. Two important parameter for the successful of P&R services are location and tarif.  In Jakarta, the successful implementation of Blok M-Kota first busway corridor could not be followed by others, due to low quality of transfer facilities. This paper reviews the theoretical ideal P&R and practical measures to be discussed for the Jakarta busway corridors.keywords: park and ride, private car users, busway